Analysis of Factors Influencing Regional Fiscal Financial Capability on Development Financing and Achieving the Level of Public Welfare in Kutai Kartanegara Regency - Alif Turiadi; Irwansyah Irwansyah; Diana Lestari (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The implementation of Regional Autonomy will encourage an increase in the welfare of the regional people, especially the poor. With Regional Autonomy, it will be easier for the poor to access resources and develop their potential to be able to increase the progress of their respective regions, so that the gap between regions and the center can be narrowed. This is because rebellions and separatist actions in the regions, according to some experts, originate from regional assessments that do not fairly receive most of the country's wealth originating from the regions. So the roots of these political demands are demands for economic justice, an unfair distribution of the cake between the center and the regions. The method used in this study is a method of quantitative data analysis and data analysis method using a path diagram with 6 dimensions of measurement, namely, factors supporting regional finance (Regional Original Income, Central Government Transfer Income, Regional Transfers, Investment, Degree of Economic Exploitation), Financing Development, and Level of People's Welfare in Kutai Kartanegara Regency in 2013-2021. Regional Own Revenue, Central Government Transfer Funds, Transfers to Regions, and Investments have a significant effect on development financing in Kutai Kartanegara Regency. However, the degree of direct economic exploitation has no significant effect on development financing and the level of welfare in Kutai Kartanegara Regency.